Semen proteome and transcriptome of the endangered black-footed ferret (Mustela nigripes) show association with the environment and fertility outcome - Nadya Ali; Olga Amelkina; Rachel M. Santymire; Klaus-Peter Koepfli; Pierre Comizzoli; Juan M. Vazquez (Scientific Reports, 2024)
Abstract The ex situ population of the endangered black-footed ferret (Mustela nigripes) has been experiencing declines in reproductive success over the past 30 years of human-managed care. A potential cause may be environmental-dependent inbreeding depression with diet being one of the contributing factors since ferrets are not fed their natural diet of prairie dogs. Here, we generated and analyzed semen proteome and transcriptome data from both wild and ex situ ferrets maintained on various diets. We identified 1757 proteins across all samples, with 149 proteins unique to the semen of wild ferrets and forming a ribosomal predicted protein–protein interaction cluster. Wild ferrets also differed from ex situ ferrets in their transcriptomic profile, showing enrichment in ribosomal RNA processing and potassium ion transport. Successful fertility outcomes documented for ex situ ferrets showed the strongest association with the semen transcriptome, with enrichment in genes involved in translation initiation and focal adhesion. Fertility also synergized with the effect of diet on differentially expressed transcriptomes, mainly affecting genes enriched in mitochondrial function. Our data and functional networks are important for understanding the causes and mechanisms of declining fertility in the ex situ ferret population and can be used as a resource for future conservation efforts.